Consultation centre services provided by the Unit of Occupational Medicine - Policlinico University of Bari Medical School - Vimercati, Luigi; Luisi, Vito; Massagli, Chiara Rosaria Stella; Schiavulli, Nunzia Anna; Macinagrossa, Linda; De Maria, Luigi; Birtolo, Francesco; Caputi, Antonio; Mansi, Francesca; Lorusso, Pietro; Gatti, Maria Franca; Intranuovo, Graziana; et al. (La Medicina del Lavoro, 2018)
The Occupational Medicine Unit , Policlinic, University of Bari Medical School, deals with diagnoses of occupational and work-related diseases. A total of 223 outpatients  examinations (180 males, 43 females) in 2016 was made , while over 4000 staff health surveillance medical examinations were performed. A high prevalence of asbestos-related diseases was observed which can be explained by the presence in the Apulia Region of several working activities with a high risk of occupational exposure to asbestos. Moreover, 72% of males with an occupational desease reported to the national insurance institution (INAIL) suffered from an asbestos-related disease. Therefore, participation in the MAREL project, which aims to create a network among  Occupational Medicine Units and INAIL, will allow the Unit to receive information from other excellence centers, and will thus provide an important contribution in terms of knowledge, disease prevention and health care quality.